The Role of Networks in SMEs in Supporting Internationalization: Literature Study - Vembri Aulia Rahmi; Sudarmiatin Sudarmiatin; Hadi Sumarsono (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The role of SMEs as the engine of the economy with all its problems is still a concern because of the contribution of sales to the overall economy. The weakness of SMEs, especially from the element of resources, results in limitations in developing the business. However, business continuity in SMEs directs companies to make business improvements, through internationalization. Meanwhile, the knowledge and skills needed by SMEs for internationalization are inadequate. Therefore, SMEs need to build a network that not only helps meet the weaknesses of UKM's resources, but can provide information and knowledge that supports internationalization. Thus, this paper is intended to provide insight into the role of networks in directing SMEs towards internationalization. The qualitative approach in this research is to use the literature study method. The results of studies from several studies on SMEs in several regions of the world explain several things regarding "networks", namely: first, how networks are able to support SMEs to achieve internationalization and explain the achievement of high international performance, through networks; second, describes the type of network in SMEs and readiness to obtain a network; third, analyzing how the business adapts and the commitment of SMEs to the network; fourth, linking the role of networking in SMEs to business success. how the network is able to support SMEs to achieve internationalization and explain the achievement of high international performance, through the network; second, describes the type of network in SMEs and readiness to obtain a network; third, analyzing how the business adapts and the commitment of SMEs to the network; fourth, linking the role of networking in SMEs to business success. how the network is able to support SMEs to achieve internationalization and explain the achievement of high international performance, through the network; second, describes the type of network in SMEs and readiness to obtain a network; third, analyzing how the business adapts and the commitment of SMEs to the network; fourth, linking the role of networking in SMEs to business success.